Effectiveness of Functional Family Therapy for Mandated Versus Non‐Mandated Youth. (September 2015) - Celinska, Katarzyna
Abstract: This study compares the outcomes for youth mandated to participate in Functional Family Therapy (FFT) to those whose participation was referred but voluntary. FFT is a short‐term intervention for delinquents and status offenders, along with their parents. The study sample consists of 120 cases: 70 youth and parents who were mandated by the Family Court to participate in FFT and 50 youth and their parents who were referred to FFT by other agencies. The sample is diverse in terms of gender, race and ethnicity. The outcome variables consist of a set of scales obtained from the Strengths and Needs Assessment (SNA). Changes in life domain functioning, child strengths, acculturation, caregivers' strengths, caregivers' needs, child behavioral emotional needs, and child risk behaviors are assessed. The analysis indicates that both groups improved across all domains. Overall, being mandated to participate in FFT does not predict greater improvements in outcomes. The findings suggest that status offenders and minor delinquents who participated in FFT could be processed less formally without foregoing the therapy outcomes.